Pulmonary atresia with ventricular septal defect and coronary artery fistula: a late presentation. Issue 3 (March 1988) - Vigneswaran, W T; Pollock, J C
Abstract : A 41 year old man presented with cyanosis and progressive shortness of breath. Cardiac angiography showed absent central pulmonary arteries, ventricular septal defect, and a fistula between the left coronary artery and pulmonary artery. Most of the blood reaching the lungs came through this fistula. An attempt at surgical palliation was unsuccessful.